2021
DOI: 10.1364/ao.427495
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh sensitive long-period fiber grating-based sensor for detection of adulterators in biofuel

Abstract: An ultra-sensitive sensor based on dual resonance long-period fiber gratings has been fabricated for the detection of methanol and water content in ethanol. The developed sensor is compact in size and light weight and employs a highly accurate spectral interrogation technique for adulterant detection, increasing its applicability compared to conventional surface plasmon resonance based sensors, which are generally expensive, as they require metal film deposition. We demonstrate that the sensor is capable of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In [31], the authors simulated how the refractive index of a methanol-ethanol solution would vary as the amount of methanol in the ethanol solution varied. This detection is made feasible by an ultra-sensitive sensor built on dual resonance long-period fiber gratings.…”
Section: Resultsmentioning
confidence: 99%
“…In [31], the authors simulated how the refractive index of a methanol-ethanol solution would vary as the amount of methanol in the ethanol solution varied. This detection is made feasible by an ultra-sensitive sensor built on dual resonance long-period fiber gratings.…”
Section: Resultsmentioning
confidence: 99%
“…For illustration, the blue line shows the presence of pure ethane gas, while the red line shows the presence of pure methane gas. The refractive index changes proportionally with the percentage of the methane-ethane mixture [66], as any percentage change in the methane and ethane mixed gases will cause a shift in the curve. Moreover, to study the sensor selectivity, we found that when working near to the absorption peaks for the interesting gas, the full width at half maximum (FWHM) increases.…”
Section: Analysis For Testing Hydrocarbon Gasesmentioning
confidence: 99%